Assessment of Quality of Internet Financial Disclosures Using a Scoring System. A Case of Polish Stock Issuers - Joanna Dyczkowska (Journal of Accounting and Management Information Systems (JAMIS), 2014)
Due to investor relations sections placed on corporate websites shareholders have an access to current information on stock issuers' activities. This enables investors to participate in discussions on decisions met by a board of a company. Transparent and comprehensible information should become, therefore, a key element of stock issuers' information policies. The paper aims at evaluating quality of Internet financial disclosures, comprising: completeness, accuracy, relevance and transparency. With a scoring method applied and with a use of appropriate weights in reference to particular criteria, a ranking of stock issuers, according to a level of disclosures, was established. The examined group consisted of 143 publicly traded Polish companies which were listed on the Warsaw Stock Exchange. Although all of them run corporate websites, almost one third did not provide any information coming directly from financial statements, whereas almost half did not disclose any financial ratios using Internet investor relations sections. The research findings indicated that few companies only could be labeled as those representing a high level of financial disclosures. Most of the examined objects were characterized by a low level of disclosures. That situation proves that despite the existence of recommended practices in a discussed area, only a small number of companies perceived corporate websites as an important communication channel with their investors. Almost one third of the research sample did not consider that way of presentation as necessary to build confidence among shareowners. The second objective of the paper was to investigate whether there existed relations between a company size, profitability or an industrial affiliation and the quality of Internet financial disclosures. Respecting results of the correlation analysis the author claims that a company size is weakly but positively correlated with the quality of financial reporting disclosures and with the total quality of Internet financial disclosures. Profitability of the examined companies was found, in turn, to be weakly but negatively correlated with the quality of financial reporting disclosures. Research findings indicated also that there were statistically valid differences in sizes of companies respecting the quality of Internet financial disclosures. Disclosures of financial reporting information, financial ratios and total Internet financial disclosures did not differ for various industries, though.
Keywords: M41; 650; investor relations; internet financial reporting; financial disclosures